Effectiveness of Cognitive-behavioral Program on Pain and Fear in School-aged Children Undergoing Intravenous Placement - Yi-Chuan Hsieh, RN, MSN; Su-Fen Cheng, RN, Ph.D; Pei-Kwei Tsay, Ph.D; Wen-Jen Su, M.D; Yen-Hua Cho, RN, BSN; Chi-Wen Chen, RN, Ph.D (Elsevier, 2017)
Summary: Purpose: This study aimed to evaluate the effects of cognitive-behavioral program on pain and medical fear in hospitalized school-aged children receiving intravenous (IV) placement. Methods: This study used an quasi-experimental design. Thirty-five participants were assigned to the experimental group and 33 to the control group in the acute internal medicine ward of a children's hospital. The cognitive-behavioral program entailed having the patients read an educational photo book about IV placement before the procedure and having them watch their favorite music video during the procedure. The outcome measures were numeric rating scales for pain intensity and fear during the procedure. Results: After applying the cognitive-behavioral program, the mean scores on pain and fear decreased in the experimental group. However, the difference in pain intensity between these two groups was nonsignificant. The intensity of fear in the experimental group was significantly lower than that in the control group. Conclusion: In this study, the cognitive-behavioral program used with school-aged hospitalized children promoted less fear during IV placement. The results of this study can serve as a reference for empirical nursing care and as care guidance for clinical IV injections involving children. Keywords: children, fear, needle, pain